The prison before the Panopticon: incarceration in ancient and modern political philosophy - Abolafia, Jacob (Harvard University Press, 2024)
"A groundbreaking history of philosophy and punishment, The Prison before the Panopticon traces the influence of ancient political philosophy on the modern institution of the prison, showing how prevailing theories of carceral rehabilitation and common justifications for the denial of liberty developed in classical and early modern thought."-- Provided by publisher